2009
DOI: 10.1128/aac.00206-09
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Heterogeneous Vancomycin-Intermediate Staphylococcus aureus Isolates from 14 Cities in China

Abstract: The prevalence of heterogeneous vancomycin-intermediate Staphylococcus aureus (hVISA) among 1,012 vancomycin-susceptible methicillin (meticillin)-resistant S. aureus isolates collected from 14 cities in China from 2005 to 2007 was 13 to 16%, as determined by a combination of (i) measurement by the modified population analysis profile-area under the curve method (PAP-AUC) and (ii) estimation from the measured sensitivity and specificity of a screening method. Two hundred isolates from blood were chosen as a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 33 publications
3
38
1
2
Order By: Relevance
“…Several studies showed that the surveillance of hVISA was not performed routinely and that the methods used differed between laboratories, thus preventing Currently, hVISA isolates are more frequently reported than previously thought. In a recent prospective study performed in France, the prevalence of hVISA was 11% (22), which is similar to previous reports (47,54) from other geographic locations. In Saudi Arabia, hVISA infection was never reported in the past, and its clinical significance appears therefore difficult to assess.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies showed that the surveillance of hVISA was not performed routinely and that the methods used differed between laboratories, thus preventing Currently, hVISA isolates are more frequently reported than previously thought. In a recent prospective study performed in France, the prevalence of hVISA was 11% (22), which is similar to previous reports (47,54) from other geographic locations. In Saudi Arabia, hVISA infection was never reported in the past, and its clinical significance appears therefore difficult to assess.…”
Section: Discussionsupporting
confidence: 89%
“…Reasons for these differences are unclear and may reflect specific MRSA subtype characteristics. However, recent MET and GRD Etest assessments performed on consecutive clinical isolates showed significantly lower sensitivities (44% to 69%) and specificities (48% to 98%) (1,17,18) than those in previous laboratorycharacterized evaluations. This suggests that some of these differences may reflect hVISA phenotype instability (22).…”
Section: Discussionmentioning
confidence: 63%
“…A modified PAP assay comparing the area under the curve (PAP-AUC) of a given strain to that of a reference heteroresistant strain was used to determine S. aureus heteroresistance to vancomycin (67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81). PAP-AUC ratios between the test and control strains of Ͻ0.9, 0.9 to 1.3, and Ͼ1.3 were considered indicative of vancomycin-susceptible S. aureus, heterogeneous vancomycinintermediate S. aureus (hVISA), and vancomycin-intermediate S. aureus (VISA), respectively (67,72,74,76).…”
Section: Population Analysis Profilingmentioning
confidence: 99%